Characterization of Pregnant Women with Heart Disease at the “Ramón Gonzalez Coro” Gynecologic and Obstetric Teaching Hospital - Yanara Gutierrez Aliaga; Ileana Chio Naranjo; Elena Guerra Chang; Marlén Rodríguez Jorge; Mario Joel Arroyo Díaz; Mayelin Díaz Gutiérrez (Medisur)
Introduction: pregnancy-related heart disease is nowadays the first cause of maternal morbidity and mortality among pregnancy-related pathologies. Objective: to characterize pregnant women with heart disease according to demographic and clinical features. Method: a descriptive study with some analytic aspects was conducted in the Heart Disease and Pregnancy service of “Ramón Gonzalez Coro’’ Gynecologic and Obstetric Teaching Hospital from 2000-2009. The universe consisted on the 472 pregnant women with heart disease that received follow up during that period. They were treated according to the protocol applied since 2000. Data were obtained through a questionnaire and were processed using the SPSS 11,5 system for Windows, through determination of absolute and relative frequencies. They included: mothers’ age, first and third trimester functional classification, drugs used and cardiovascular complications. Results: valvular heart diseases (25, 6 %) were the most common type of heart disease. Important modifications were found at the end of pregnancy for the functional degree. Complications were registered in 29,9 % of patients, being pulmonary acute edema (6,4 %), cardiac arrest (4,3 %) and arrhythmias (3,5 %), the most common ones. Pulmonary thomboembolism was the cause of the two maternal deaths that occurred. Conclusion: valvular heart diseases were the most common cardiac disease detected in the patients included in our study. Most of them were classified as functional degree I, being pregnancy a potential risk for them.